GANDRUNG AS A POLITICAL COMMUNICATION TOOL IN BANYUWANGI (A Study of Antonio Gramsci's Hegemony): GANDRUNG SEBAGAI ALAT KOMUNIKASI POLITIK DI BANYUWANGI (Suatu Kajian Hegemoni Antonio Gramsci) - Mahfud; Andrik Purwasito; Warto; Wakit Abdullah Rais (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Gandrung is one of the oldest forms of performing arts in Banyuwangi. Gandrung becomes a symbol of political communication through culture. This is clearly seen during the democratic party period. The purpose of this research is to reveal and criticize Gandrung which is used as a medium of political communication by political actors in Banyuwangi. The form of this research is descriptive qualitative. The theory used is Gramsci's hegemony. Data collection techniques using interviews, observation, and content analysis. The data analysis technique used in this study is an interactive analysis. The results of the study show that the high creativity of the people of Banyuwangi in folk art is recognized by the local government. This has become a loophole for political actors in Banyuwangi to insert political messages into Gandrung art performances. Thus, these political messages can be easily accepted by the public. This proves that if Gandrung's art is studied using Gramsi's theory, it shows that Gandrung is totally hegemony. Total hegemony is characterized by close to total mass affiliation. Society shows a strong degree of moral and intellectual unity, which is evident from the organic relationship between the government and the governed. This relationship is not colored by contradictions and antagonisms either socially or ethically.